How Emotion Matters in Four Key Relationships in Teaching and Learning in Higher Education. Issue 3 (2nd July 2016) - Quinlan, Kathleen M.
ABSTRACT: The role of emotions in learning and teaching has largely been neglected in educational literature, particularly in higher education. Yet there are signs of increased interest in emotions in recent literature. This paper argues that emotions are a vital aspect of relationships. How we feel with and about others is central to the quality of those relationships. Thus, emotions matter in college teaching and learning as an aspect of enriching social and relational experiences that support student development. This paper discusses four key relationships in higher education: students with subject matter; students with teachers; students with other students; and students with their developing selves. For each key relationship, key literature is referenced, and suggestions for enhancing practice are offered.